The role of demethylases in cardiac development and disease. (September 2021) - Davis, Kathryn; Azarcon, Presley; Hickenlooper, Samuel; Bia, Ryan; Horiuchi, Emilee; Szulik, Marta W.; Franklin, Sarah
Abstract: Heart failure is a worldwide health condition that currently has limited noninvasive treatments. Heart disease includes both structural and molecular remodeling of the heart which is driven by alterations in gene expression in the cardiomyocyte. Therefore, understanding the regulatory mechanisms which instigate these changes in gene expression and constitute the foundation for pathological remodeling may be beneficial for developing new treatments for heart disease. These gene expression changes are largely preceded by epigenetic alterations to chromatin, including the post-translational modification of histones such as methylation, which alters chromatin to be more or less accessible for transcription factors or regulatory proteins to bind and modify gene expression. Methylation was once thought to be a permanent mark placed on histone or non-histone targets by methyltransferases, but is now understood to be a reversible process after the discovery of the first demethylase, KDM1A/LSD1. Since this time, it has been shown that demethylases play key roles in embryonic development, in maintaining cellular homeostasis and disease progression. However, the role of demethylases in the fetal and adult heart remains largely unknown. In this review, we have compiled data on the 33 mammalian demethylases that have been identified to date and evaluate their expression in the embryonic and adult heart as well as changes in expression in the failing myocardium using publicly available RNA-sequencing and proteomic datasets. Our analysis detected expression of 14 demethylases in the normal fetal heart, and 5 demethylases in the normal adult heart. Moreover, 8 demethylases displayed differential expression in the diseased human heart compared to healthy hearts. We then examined the literature regarding these demethylases and provide phenotypic information of 13 demethylases that have been functionally interrogated in some way in the heart. Lastly, we describe the 6 arginine and lysine residues on histones which have been shown to be methylated but have no corresponding demethylase identified which removes these methyl marks. Overall, this review highlights our current knowledge on the role of demethylases, their importance in cardiac development and pathophysiology and provides evidence for the use of pharmacological inhibitors to combat disease. Highlights: Epigenetic regulation of the heart by demethylases is relatively new field of study. There is differential expression of demethylases during human heart disease in RNA-seq and proteomics datasets. Demethylases play important roles in both heart development and heart disease. Regulation of demethylases via small molecular inhibitors may be relevant therapeutics for heart disease.